Gut microbiome associated with melanin deposition by supporting energy metabolism in Sichuan mountainous black-bone chickens - Liao, Juan; Duan, Ling; Wang, Gang; Yu, Shigang; Shen, Xuemei; Jiang, Min; Shen, Ke; Singla, Rajeev K.; Shen, Bairong; Zhou, Yi (Frontiers in Microbiology, 2025)
IntroductionVariation in melanin deposition profoundly influences the economic value of Sichuan mountainous black-boned chickens; however, the contribution of the gut microbiome in modulating this process remains poorly understood. This study aimed to characterize the gut microbiome in Sichuan mountainous black-boned chickens with distinct skin color brightness (quantified by colorimeter) and to explore its association with melanin deposition.MethodsCecal microbiota composition was profiled using 16S rRNA sequencing in dark-skinned (BlackD) and light-skinned (BlackL) groups. Serum metabolic profiles were determined via untargeted metabolomics. Differential abundance of bacterial genera was assessed, followed by pathway enrichment analysis (KEGG and MetaCyc). Associations between microbiome, metabolites, and melanin-related pathways were evaluated.ResultsThe BlackD group exhibited higher alpha diversity and significant alterations in 10 bacterial genera (primarily linked to short-chain fatty acid metabolism and melanin-related metabolites) compared to the BlackL group. Pathway enrichment showed upregulation of energy metabolism-related KEGG pathways (AMPK signaling, insulin signaling, thyroid hormone signaling) and MetaCyc pathways in BlackD. Untargeted serum metabolomics revealed elevated melanin-related metabolites in BlackD, including L-Tyrosine, L-DOPA, and Dopaquinone. Gut microbiome and serum metabolite profiles in BlackD were strongly correlated with enhanced energy metabolism.DiscussionThe gut microbiome may influence melanin deposition by modulating host metabolic activity, with microbiome-derived metabolites supporting the high energy demands of melanocyte activity. These findings uncover a potential mechanism linking microbial composition to phenotypic variation in melanin deposition.